IKZF3 is a novel prognostic biomarker for head and neck squamous cell carcinoma: A study based on bioinformatics analysis. Issue 11 (17th March 2023) - Li, Hongxiang; Ye, Mengmeng; Hu, Zeyang; Lu, Haoxuan; Zheng, Dawei; Wu, Mi; Ge, Ting; Xu, Shuguang; Ge, Zhen; Zhang, Shuoni; Xu, Guodong; Chen, Hang
Abstract : In the past few years, immunotherapy of tumors has become an extensive research hotspot, and the value of IKZF family genes in the tumor microenvironment has also been increasingly recognized. However, the expression of the IKAROS family zinc finger 3 (IKZF3) gene in human head and neck squamous cell carcinoma (HNSCC) and its prognostic value were not reported for the main subset until now. In the present study, we analyzed the relationship between IKZF3 gene expression and the survival of HNSCC patients. To evaluate the potential of IKZF3 as a prognostic biomarker for HNSCC comprehensively, multiple online analysis tools, including UALCAN, cBioPortal, GEPIA, WebGestalt, String, Genomic Data Commons, and TIMER databases were utilized in our study. We observed that the HNSCC patients with higher IKZF3 expression tended to exhibit longer overall survival. Univariate and multivariate Cox regression analyses indicated that age and grade were independent prognostic indicators in HNSCC. Moreover, Gene Ontology and KEGG function enrichment analyses showed that several pathways in HNSCC might be pivotal pathways regulated by IKZF3, which revealed that IKZF3 was probably participating in the occurrence and development of HNSCC. Furthermore, the hypomethylation of the IKZF3 gene was closely associated with genes that observed mutation in HNSCC. IKZF3 was significantly correlated with several immune cells in HNSCC (e.g., CD8 + T cell, CD4 + cell, and dendritic cell). We explored the potential prognostic values and roles of the IKZF3 in HNSCC, revealing that IKZF3 was probably a novel and reliable prognostic biomarker for patients with HNSCC.